Petersen-colorings and some families of snarks - Hägglund, Jonas (Ars mathematica contemporanea, 2014)
In this paper we study Petersen-colorings and strong Petersen-colorings on some well known families of snarks, e.g. Blanuša snarks, Goldberg snarks and flower snarks. In particular, it is shown that flower snarks have a Petersen-coloring but they do not have a strong Petersen-coloring. Furthermore it is proved that possible minimum counterexamples to Jaegers Petersen-coloring conjecture do not contain a specific subdivision of ?$K_{3, 3}$?.
Keywords: Petersen colorings; snarks; strong Petersen colorings